Intervensi Tuhan dalam Keterlibatan Orang tua terhadap Gaya Belajar Generasi Pembelajar Mandiri (Homeschooling) - Chanita Christie (REDOMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
The success of the child's growth and development process is an important task for parents in accompanying and guiding children to reach the top of the destiny of every talent, passion and longing to be realized. With world conditions that are not getting better, even if technology is getting better and even starting to replace the roles and functions of humans in carrying out the process of daily activities. It really creates a lot of new problems, especially for the future generations of God's church in the future. Parents as the holder of an important role in the process of growth and development and formation of children's character are expected to become a dependent place for children in the world as representatives of God on earth. The author uses the literature study method to describe the form of God's intervention in parental involvement in the learning style of the Self-Learning Generation (Homeschooling). Through literature studies by reading books, the author can formulate a useful view of God's intervention in parental involvement in the Learning Style of the Independent Learning Generation (Homeschooling).AbstrakKeberhasilan proses tumbuh kembang anak merupakan tugas penting orang tua dalam mendampingi dan menuntun anak mencapai puncak destiny dari setiap talenta, passion dan kerinduannya terwujud. Dengan kondisi dunia yang semakin tidak membaik, sekalipun teknologi semakin membaik dan bahkan mulai menggantikan peran dan fungsi manusia dalam menjalani proses kegiatan keseharian.  Sungguh itu membuat banyak masalah-masalah baru, terutama bagi masa depan generasi gereja Tuhan dimasa yang akan datang. Orang tua sebagai pemegang peranan penting dalam proses tumbuh kembang dan pembentukan karakter anak, sangat diharapkan dapat menjadi tempat bergantung anak di dunia selayaknya representatif Tuhan di bumi. Penulis menggunakan metode studi literatur untuk mendiskripsikan bentuk intervensi Tuhan dalam keterlibatan orang tua terhadap gaya belajar Gegnerasi Pembelajar Mandiri (Homeschooling). Melalui kajian Pustaka dengan membaca buku-buku maka penulis dapat merumuskan suatu pandangan yang bermanfaat tentang intervensi Tuhan dalam keterlibatan orang tua terhadap Gaya Belajar Generasi Pembelajar Mandiri (Homeschooling).